Korteks Prefrontal pada Kelompok Remaja Adiksi Pornografi Lebih Kecil dibandingkan Remaja Tanpa Adiksi Pornografi - Prawiroharjo, Pukovisa; Edmi Edison, Rizki; Ellydar, Hainah; Pratama, Peter; Evangeline Imelda Suaidy, Sitti; Amani, Nya'Zata; Carissima, Diavitri; Faradisa Hatta, Ghina (PERDOSNI, 2023)
Background and aims: Increasing popularity of Internet has exposed our children pornography addiction. As in other types of addiction, it affects a brain region known as prefrontal cortex (PFC), which is important in executive functions and inhibitory control. However, this region was loosely defined, and there was no consensus for that definition. We aimed to use volumetric MRI in finding the defining region of PFC which would be suitable in distinguishing pornography addicted juveniles. Methods: We enrolled 30 juveniles (12-16 y.o.) consisting of 15 pornography addiction and 15 non-addiction subjects. We proposed several models of PFC definition from mix-and-matched subregions, consisting of orbitofrontal (OFC), inferior frontal gyrus (IFG; pars orbitalis, opercularis, and triangularis), dorsolateral PFC (DLPFC), and anterior cingulate (ACC). Suitable PFC definition was defined as models which volume statistically different between both groups. Brain volumetric was measured using 3D-T1 3T MRI images and analyzed using FreeSurferÃ‚Â® for automatic cortical reconstruction and brain segmentation (recon-all command). Results: We found significant differences between groups in 6 models, which mainly included OFC, ACC, and DLPFC, with models devoid of DLPFC had lowest mean differences. Conclusion: The most suitable definition of PFC for pornography addiction study should consist of OFC, ACC, and especially DLPFC. Inferior frontal gyrus pars orbitalis was not necessary for this purpose, but may increase effect size if it is included.